Tantangan UKM Menghadapi Pandemi Covid-19: Pengaruh Kepemimpinan dan Pelatihan terhadap Kinerja - Mei Rani Amalia (UNIVERSITAS PGRI MADIUN, 2021)
SMES have a very important role, so it can be said that SMES are the backbone of the Indonesian economy. BPS Data informs that about 99% of existing business units are SMES capable of absorbing manpower about 96.3% of the amount of productive workforce available. But since the outbreak of Covid-19 struck Indonesia from the end of December 2019, the business of SMES is one of the most experienced sectors, such as sales that go down, difficult to obtain raw materials, the disbanding of production and capital are some of the perceived effects of SMES during the pandemic. To be able to continue to maintain its performance, it takes good cooperation from all parties from government, private, and community participation. This research is conducted with the aim to know the impact of training and leadership on the performance of SME Kab. Tegal during the Covid-19 pandemic. The study took 100 random samples and data collection was conducted through observations, interviews, and questionnaires. Data analysis methods use multiple linear regression analyses. The results showed that partial training had no significant effect on performance, while leadership had a significant influence on MSME performance. Simultaneously the training and leadership significantly affect the performance of SME Kab. Tegal during the Covid-19 pandemic. Training to the SMES will help improve the performance during the pandemic. Keywords: SMES, leadership, training, pandemic covid-19, performance